IMPLEMENTASI PEMBELAJARAN MEMBACA AL-QUR’AN MELALUI METODE THORIQOTY DI SEKOLAH DASAR BRAWIJAYA SMART SCHOOL KOTA MALANG - Kiki Mamlu’atul Karimah; Mohammad Afifulloh; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Education is very important for us in the era of globalization. So it is true that education is an effort made to improve in all its aspects, therefore from some of the education that teachers have given to students in primary schools there is one religious education that is very poorly paid attention to by parents. Namely the education of reading the Al-Qur’an. Because ini general parents only focus on children about general education and very rarely for parents to pay attention to one of religious education, namely learning to read the Al-Qur’an. So that seen from the development of students, especially at the elementary school level is very lacking in reading the Al-Qur’an in accordance with the rules and also the knowledge of recitation correctly and correctly. For that in the current era of globalization, learning the Al-Qur’an is needed in the world of education both formal and non-formal schools for elementary school children. So from there the primary school BSS (Brawijaya Smart School) agreed to hold a activity learning Al-Qur’an using the Thoriqoty method which was carried out every morning. With this activity in the school BSS (Brawijaya Smart School) hopes that later students will be able to read teh Al-Qur’an properly and correctly.